Workplace Physical Violence against the Pre-hospital Emergency Staff in Guilan Province - Ali Golzare Zahmatkesh Sanggouei; Majid Pourshaikhian; Mohammad Esmaeilpour Bandboni; Mohammad Taghi Moghadamnia; Ehsan Kazem Nezhad Leyli; Fateme Hasandoost (Guilan University of Medical Sciences, 2018)
Abstract Introduction: Workplace violence is one of the problems faced by health care workers. Pre-hospital emergency staff is exposed to workplace violence, according to their working conditions. Understanding the nature of workplace violence plays a fundamental role in its prevention and management. Objective: This study was conducted to determine the frequency of workplace physical violence against pre-hospital emergency staff and its relationship with some demographic variables. Materials and Methods: This descriptive analytical cross-sectional study was performed on 130 pre-hospital emergency medical staff, selected on the basis of random sampling in the Guilan province in 2014, using a standard questionnaire on violence against health care staff, developed by the International Labour Organization, the Nursing High Council, the World Health Organization, and the International Public Service in 2002. The data analysis was performed using descriptive statistics, Chi-square and Fisher exact tests, as well as Logistic regression. Results: The results showed that 34.51% of the subjects experienced physical violence in the past year. The findings also showed that there was a significant relationship between the incidence of physical violence and marital (p = 0.008), age (p = 0.04), and higher work experience variables (p = 0.04). Conclusion: There is a prevalent workplace physical violence against pre-hospital emergency staff, causing individual and organizational complications. This issue should be addressed by emergency managers and preventive measures should be taken to improve the safety of the staff and the productivity of the organization.